EXPLORING THE CULTURAL VALUES OF “SAEMAUL UNDONG” AND “GOTONG ROYONG” AS THE DEVELOPMENT OF AN ANTI-CORRUPTION CULTURE: Socio-Economic Studies in East Asia and Southeast Asia - Rostamaji Korniawan (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
The traditions of Saemaul Undong and Gotong Royong are the cultures of South Korea and Indonesia which are considered providing added value to their local communities in restricting themselves from any corrupt behavior. Through discussions about the traditions of Saemaul Undong and Gotong Royong, this study aims to explore these two different cultures. This is intended to find the cultural values of local communities that have universal values. These values are then believed and used to deal with and prevent the corrupt behavior of the community. This study was conducted using qualitative method through comparative historical and literary approaches. From the literature review, it is found that pedagogy, cooperation, leadership, equality, and nationalism are values that support the community to have a noble attitude that is able to control someone to not commit corrupt actions. However, both South Korea and Indonesia must struggle to deal with the corrupt behavior that still occurs today.